After the Crisis? - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank Group, discussed the implications of the 2009 financial upheaval that is changing our world. He addressed the following: (i) what are the perceptions and realities of power after this crisis?; (ii) will the U.S. dollar remain the predominant reserve currency?; (iii) will democratic governments permit independent central banks to assume even more authority?; (iv) is the global trading system keeping up with the demands of the global economy?; and (v) what will be the role of developing countries after the crisis? He stressed the opportunity to craft a new system of “Responsible Globalization” allowing balanced growth, financial stability, countering climate change, and advancing opportunities for the poorest.